2005
DOI: 10.3168/jds.s0022-0302(05)72719-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Albumin in Nonhepatic Tissues and its Synthesis by the Bovine Mammary Gland

Abstract: Albumin is a well-characterized product of the liver. In the present study, objectives were to determine if the albumin gene is also expressed in various nonhepatic tissues in the bovine; whether mammary gland epithelial cells synthesize albumin; and how its synthesis is affected by bovine mastitis. Albumin expression was monitored using reverse transcription-polymerase chain reaction. Tissues examined were: liver, mammary gland, tongue, intestine, lymph gland, testicle, ovary, and uterus. All tissues except t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 26 publications
5
68
2
2
Order By: Relevance
“…Albumin levels were significantly higher (P<0.0001) in infected glands than in healthy glands (Table 1, Fig.2), thus confirming an increase in vascular permeability and the passage of blood albumin to the mammary glands (Paape et al 1995, Shirazi-Beheshtiha 2012. This observation may also be attributable to the production of albumin by the gland itself, as observed by Shamay et al (2005), suggesting that albumin secretion in the mammary gland is part of a non-specific defense system.…”
Section: Discussion Total Proteinsupporting
confidence: 63%
“…Albumin levels were significantly higher (P<0.0001) in infected glands than in healthy glands (Table 1, Fig.2), thus confirming an increase in vascular permeability and the passage of blood albumin to the mammary glands (Paape et al 1995, Shirazi-Beheshtiha 2012. This observation may also be attributable to the production of albumin by the gland itself, as observed by Shamay et al (2005), suggesting that albumin secretion in the mammary gland is part of a non-specific defense system.…”
Section: Discussion Total Proteinsupporting
confidence: 63%
“…However, other evidence suggested that the goat mammary gland is able to synthesize a portion of the milk albumin [98]. Expression of albumin in the bovine mammary gland has been previously reported and studied in dairy cows [99]. Observations of increased albumin expression in mammary tissue explants challenged with lipopolysaccharides, and a higher expression observed in glands with mastitis, have led to the suggestion that albumin may have a role in the innate nonspecific defense system [99].…”
Section: Figurementioning
confidence: 99%
“…Expression of albumin in the bovine mammary gland has been previously reported and studied in dairy cows [99]. Observations of increased albumin expression in mammary tissue explants challenged with lipopolysaccharides, and a higher expression observed in glands with mastitis, have led to the suggestion that albumin may have a role in the innate nonspecific defense system [99]. In all species where albumin mRNA was available (i.e., all except kangaroo, Figure 1) a level of expression was detected by the microarray platforms even though at very low levels compared to the highly abundant milk proteins.…”
Section: Figurementioning
confidence: 99%
“…Variations in milk serum albumin concentrations is a frequently used marker of exudation of plasma. A low concentration of BSA, around 0.2 mg/mL compared to the 40-45 mg/mL in plasma, is found in the milk of healthy glands, probably leaking from the blood, although part of it may be secreted by the MEC [166]. The increase in serum albumin concentrations is an early event in case of clinical mastitis, temporally coincident with the influx of cells [7,153,170].…”
Section: Humoral Defensesmentioning
confidence: 99%